2008
DOI: 10.2190/cs.9.4.e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supplemental Instruction on Students in Stem Courses: Results from San Francisco State University

Abstract: Comparisons between participants and non-participants in supplemental instruction classes at San Francisco State University over a six-year period show positive impacts in terms of increased student performance and progression through subsequent courses in a sequence, despite the lower academic indicators of the supplemental instruction participants. More females participated than were represented in the course as a whole, but the effects were greater for males. Effects were particularly striking for students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 5 publications
4
49
0
Order By: Relevance
“…Also, despite showing better performance, SI takers typically seem to have lower academic indicators than their peers in terms of SAT I and ACT scores (Hensen and Shelley, 2003); the increase in performance associated with taking SI does not seem to be due to academically stronger students self-selecting into the program. The results of SI use at SFSU show the same patterns, albeit with some variation by course type (Peterfreund et al, 2007).…”
Section: Addressing the Problemmentioning
confidence: 56%
See 2 more Smart Citations
“…Also, despite showing better performance, SI takers typically seem to have lower academic indicators than their peers in terms of SAT I and ACT scores (Hensen and Shelley, 2003); the increase in performance associated with taking SI does not seem to be due to academically stronger students self-selecting into the program. The results of SI use at SFSU show the same patterns, albeit with some variation by course type (Peterfreund et al, 2007).…”
Section: Addressing the Problemmentioning
confidence: 56%
“…These outcomes would contribute to addressing underrepresentation of these groups among SFSU biology graduates. Our analysis of the effects of SI at SFSU from its inception in spring 1999 through spring 2005 (detailed in Peterfreund et al, 2007) found something much more surprising. We did indeed find substantial SI benefits among all groups, but the benefits among the URM population were higher than among all others, particularly in the critical Introductory Biology I course.…”
Section: Addressing the Problemmentioning
confidence: 88%
See 1 more Smart Citation
“…Out-of-class supplemental instruction sessions are facilitated by senior students (peers) who have successfully completed the target course, and students are encouraged to work cooperatively on materials that supplement and enrich course material. These are complemented by training on study skills, embedded into the context of the supported course (Peterfreund et al 2008). All supplemental instruction facilitators undergo thorough training prior to the facilitation of supplemental instruction sessions.…”
Section: The Supplemental Instruction Modelmentioning
confidence: 99%
“…Peer-assisted learning is a well-established method for promoting student learning, and has a long tradition in higher education around the world (Anderson, Boud, and Sampson 1996;Magin and Churches 1995;Medina 2003;Peterfreund et al 2008;Potter 1997;Widmar 1994;Wood 1997). A variety of different peer-assisted learning methods have previously been described (see Roscoe and Chi 2007), including the 'traditional' mode, which is also known as supplemental instruction, and encompasses a certain hierarchy of educational levels, where a senior student tutors a group of junior students (Blanc, DeBuhr, and Martin 1983;Martin and Blanc 1981); and the more innovative (unconventional) mode where same-year students form a learning group with the goal of teaching one another.…”
Section: Introductionmentioning
confidence: 99%